1992
DOI: 10.1002/app.1992.070450804
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet‐radiation‐induced graft copolymerization of styrene and acrylonitrile onto cotton cellulose

Abstract: SYNOPSISPhotoinitiated graft copolymerization of the vinyl monomers, styrene and acrylonitrile, onto cotton cellulose was studied using uranyl nitrate and ceric ammonium nitrate as photoinitiators. Uranyl nitrate photoinitiation showed a higher level of grafting for styrene, whereas in the case of acrylonitrile ceric ammonium nitrate was found to be the better photoinitiator. Optimized conditions of grafting, when employed to cotton swollen with sodium hydroxide and zinc chloride, enhanced the graft levels for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…Besides, the observed leveling off of the values of % G beyond 6h could be attributed to a decrease in concentration for both photo‐initiator and monomer, thereby causing a reduction in the number of sites on the backbone available for photo‐grafting as the reaction proceeded. Similar time dependency of grafting yields was reported by other workers …”
Section: Resultssupporting
confidence: 90%
“…Besides, the observed leveling off of the values of % G beyond 6h could be attributed to a decrease in concentration for both photo‐initiator and monomer, thereby causing a reduction in the number of sites on the backbone available for photo‐grafting as the reaction proceeded. Similar time dependency of grafting yields was reported by other workers …”
Section: Resultssupporting
confidence: 90%
“…In these studies, however, no systematic characterization of products was reported. It was reported that thermal resistance of the grafted copolymer was improved 18–22. In these studies too, characterization of samples are not enough or thermal analysis data are not fully compared with component homopolymers, i.e., cellulose and polyacrylonitrile.…”
Section: Introductionmentioning
confidence: 99%
“…Many workers investigated the thermal decomposition behavior of the grafted cellulose products. However, grafting reactions were carried out in heterogeneous3–6 and homogeneous reaction conditions and all the reported homogeneous reactions were investigated in solvent systems like dimethyl sulfoxide and paraformaldehyde (DMSO/PF) 7, 8, 11, 12. It was reported that crystallinity, crystal size, and degree of polymerization of cellulose greatly affect the pyrrolysis kinetics of high α‐cellulose,9, 10, 13 attributed to the synthetic polymer chains hindering the crystallization of cellulose chain.…”
Section: Introductionmentioning
confidence: 99%